2009
DOI: 10.1158/0008-5472.sabcs-09-203
|View full text |Cite
|
Sign up to set email alerts
|

SUCON Trial (SUnitinib CONsolidation Therapy in Metastatic Breast Cancer): A Belgian Multicenter Phase II Randomized Trial in Her2 Negative Metastatic Breast Cancer Evaluating Consolidation Antiangiogenic Therapy with Sunitinib after Objective Response to Taxane Chemotherapy.

Abstract: Under the auspices of the Belgian Society of Medical Oncology (BSMO).Background: New drugs are generally tested in patients with metastatic disease where bulky tumor mass is present. However, antiangiogenic compounds are probably more beneficial in the prevention of regrowth from tumors with small tumor load than in bulky tumors. This study wants to test the hypothesis that antiangiogenic compounds such as sunitinib are able to delay tumor progression after tumor mass reduction by taxanes, i.e. an objective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Final results from a randomized phase II study (SABRE-B) showed that the addition of sunitinib to the approved paclitaxel plus bevacizumab regimen first-line was poorly tolerated, and the study was closed prematurely [ 75 ]. In addition, the results of the SUCON trial failed to demonstrate that sunitinib delays tumor progression following an objective response to taxane therapy [ 76 ].…”
Section: Other Investigational Targeted Therapy Regimensmentioning
confidence: 99%
“…Final results from a randomized phase II study (SABRE-B) showed that the addition of sunitinib to the approved paclitaxel plus bevacizumab regimen first-line was poorly tolerated, and the study was closed prematurely [ 75 ]. In addition, the results of the SUCON trial failed to demonstrate that sunitinib delays tumor progression following an objective response to taxane therapy [ 76 ].…”
Section: Other Investigational Targeted Therapy Regimensmentioning
confidence: 99%
“…A phase II trial demonstrated 11% PR and 5% SD among 64 patients with refractory, late-stage MBC receiving sunitinib as mono-therapy; median time to progression and OS were 10 and 38 weeks, respectively [ 49 ]. All phase I/II studies of sunitinib in combination with chemotherapy have shown activity and manageable toxicities [ 49 - 53 ]. However, a phase III study of sunitinib plus paclitaxel versus bevacizumab plus paclitaxel as first-line therapy in ABC (NCT00373256) has been terminated prematurely as it would not have met its primary goal (the primary endpoint being PFS).…”
Section: Inhibitors Of Other Receptors Related To Angiogenesis: Tyrosmentioning
confidence: 99%
“…Thus, phase II randomised trials including sorafenib or axtinib have shown increased PFS [ 60 , 71 ]. On the other hand, other trials have been negative [ 66 , 67 ] and accumulated data from recent trials did not support the use of sunitinib in the treatment of MBC [ 53 - 56 ]. The reason for the lack of effect is probably multifactorial.…”
Section: Inhibitors Of Other Receptors Related To Angiogenesis: Tyrosmentioning
confidence: 99%